THE INSTRUCTIONAL MATERIAL OF TEACHING ENGLISH IN MI PSM GAMBYOK: A STUDY ON THE INSTRUCTIONAL DESIGN - Yopi Arianto (JURNAL KOULUTUS, 2019)
Abstract Teaching English for the students in the elementary level should be meaningful and fun. By learning in a great atmosphere, the students are expected to understand well the materials. Most of the elementary schools in east java put English as the lesson, start from the first grade. A good decision but in the application, most English teachers don‘t use the proper method. This condition makes the learning process in vain. Condition stated is also occurs in MI PSM Gambyok. The research describes this condition using the instructional design point of view in the descriptive research. The school has problem with the teaching method which shows by the score in daily test are good (up to 7) but centered-test like middle test or final test are bad (below 5). It shows that the trouble is in the teaching method. This research finds that the teacher do the same activities trough the same instructions with the different materials. The problem wouldn‘t be solved, if the teacher still used the same instructions. Key words: Instructional materials, learning process, method